Cement dosage and compressive strength correlation in rammed earth walls: a case study - Ariza Flores, Victor Andre (2023)
In this study, we investigated the correlation and development of a linear regression model between the variables "added cement" and "compressive strength of rammed earth walls" constructed with aggregates obtained from Colpa Alta, Huánuco, Peru through bivariate analysis and multivariate data analysis. This analysis was motivated by the increasing difficulty for the local population to build confined masonry housing due to the increase in the prices of building materials brought on by the COVID-19 pandemic. In this context, rammed earth walls offer a more affordable alternative to the traditional system, although it is necessary to improve their structural capacity. 60 samples of aggregates were collected in situ, following the Peruvian Technical Standard E-080. Subsequently, they were divided into four groups of 15 samples each, where 5%, 10% and 15% of the aggregate were replaced by cement. Compressive strength tests were performed, and the results were analysed using statistical techniques. The findings revealed a significant increase in compressive strength in samples containing cement compared to conventional rammed earth blocks. It was obtained that there is a strong correlation between the variable "added cement" and "compressive strength of rammed earth walls".  The linear regression model quantitatively explained the influence of cement on compressive strength.